2016
DOI: 10.1097/md.0000000000004881
|View full text |Cite
|
Sign up to set email alerts
|

Patients with end-stage renal disease were at an increased risk of hospitalization for acute diverticulitis

Abstract: Patients with end-stage renal disease (ESRD) show a high incidence of bacterial translocation and impaired gastrointestinal motility. The intestinal tract is believed to be the most crucial source of translocated bacteria. To evaluate the risk of colonic diverticulitis in patients with ESRD, we conducted a nationwide population-based cohort study. Patients who met the following 3 criteria were defined as patients with ESRD: patients diagnosed with ESRD who received regular hemodialysis between 2000 and 2005, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…Regarding drugs, the potential protective effect of calcium channel blockers in reducing the rate of diverticular complications observed in case-control analyses 37 , 47 needs to be confirmed. Also, the recent epidemiological evidence that reports a higher prevalence of AD among women older than 50 years of age 11 , 48 , younger individuals 5 , 11 , 13 , and patients with end-stage renal disease 49 , as well as the association of cardiovascular disease and chronic obstructive pulmonary disease with complicated DD 28 , 50 , needs to be confirmed and explained.…”
Section: Risk Factors For Acute Diverticulitis and Relative Recurrencmentioning
confidence: 98%
“…Regarding drugs, the potential protective effect of calcium channel blockers in reducing the rate of diverticular complications observed in case-control analyses 37 , 47 needs to be confirmed. Also, the recent epidemiological evidence that reports a higher prevalence of AD among women older than 50 years of age 11 , 48 , younger individuals 5 , 11 , 13 , and patients with end-stage renal disease 49 , as well as the association of cardiovascular disease and chronic obstructive pulmonary disease with complicated DD 28 , 50 , needs to be confirmed and explained.…”
Section: Risk Factors For Acute Diverticulitis and Relative Recurrencmentioning
confidence: 98%
“…This is also consistent with results of previous reports. Chang et al reported that patients with ESRD has higher incidence of acute colonic diverticulitis, higher rates of surgical interventions and mortality [ 20 ]. Morris et al studied the incidence of perforated diverticulitis and risk factors for death in a UK population.…”
Section: Discussionmentioning
confidence: 99%
“…Patienten mit verschiedenen Nierenerkrankungen im Endstadium unter Dialysebehandlung (n = 32 000) hatten eine eindrucksvoll höhere kumulative Inzidenz für eine akute Divertikulitis als gematschte Kontrollen. Das Risiko war nach Adaptation an alle möglichen Risikofaktoren um den Faktor 11,2 größer [112].…”
Section: Arterielle Hypertonieunclassified
“…Multimorbidität ist als ein gesonderter Risikofaktor von erheblicher Bedeutung zu werten. Arbeiten über den Charlson Komorbiditäts Index (> 3) als Risikoindikator bei der Divertikelkrankheit geben davon Zeugnis [112]. Eine weitere Publikation bestätigt nicht nur den prädiktiven Wert des Charlson Index für die Schwere einer Divertikulitis sondern auch die des American Society of Anesthesiologists (ASA) Physical Status Classification Scores (ASA) [131].…”
Section: Multimorbiditätunclassified